2013
DOI: 10.1055/s-0033-1345430
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Thumb Sensibility with Innervated Reverse Homodigital Dorsoradial Flap

Abstract: Innervated reverse homodigital dorsoradial flap serves as a reliable and sensate flap for extensive thumb soft tissue reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…15 Its reconstructive sites include the pulp, radial, and dorsal aspect of the distal phalanx, unlike the dorsoulnar flap, which is used mostly for tip injuries, and it holds the possibility of neurorrhaphy of the dorsal collateral nerve to the recipient sites, albeit with no proven benefit. 28…”
Section: Discussionmentioning
confidence: 99%
“…15 Its reconstructive sites include the pulp, radial, and dorsal aspect of the distal phalanx, unlike the dorsoulnar flap, which is used mostly for tip injuries, and it holds the possibility of neurorrhaphy of the dorsal collateral nerve to the recipient sites, albeit with no proven benefit. 28…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35] Some researchers reported constant observation in all cadaver dissections and clinical cases. 13,14,16 In our clinical practice, we never deliberately dissected the artery. Alternatively, we designed the flap and the route of pedicle based on the results of Doppler probe and dissected the pedicle as wide as possible.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, exposure of deep structures, such as joints, bones, or tendons, is an emergency situation that requires a reliable coverage technique. 8 Reviews have previously reported a variety of closure techniques for digital defects, such as V-Y advancement flaps, cross-finger flaps, neurovascular island flaps, and dorsal metacarpal artery flaps. 8,9 The V-Y advancement flap is suited for transverse plane or volar oblique injuries, and the obvious advantages for it are its simplicity and association with little trauma.…”
Section: Discussionmentioning
confidence: 99%
“…8 Reviews have previously reported a variety of closure techniques for digital defects, such as V-Y advancement flaps, cross-finger flaps, neurovascular island flaps, and dorsal metacarpal artery flaps. 8,9 The V-Y advancement flap is suited for transverse plane or volar oblique injuries, and the obvious advantages for it are its simplicity and association with little trauma. However, the distance this flap can be advanced to is limited, so it is not recommended when the length of skin loss exceeds 1.5 cm.…”
Section: Discussionmentioning
confidence: 99%